Principales desafíos que enfrentaría Costa Rica en materia de capital humano y plataformas tecnológicas al implementar una Política de Desarrollo de Clústeres - Leitón-Elizondo, Silvia Paola (Instituto Tecnológico de Costa Rica, 2018)
The purpose of this research is to examine the main challenges that Costa Rica would face in terms of human capital and technological platforms to implement a Cluster Development Policy. The Cluster Development Policy created in the Autonomous Community of the Basque Country, which was created in the 90's by Michael Porter, was used as the main foundation. The design of the research corresponds to an action research study, because it will provide an investigation to subsequently create the action which would be the public policy on Cluster Development. In addition, national and international experts were queried to have a national and international expectation. The data collection was executed through face-to-face interviews. The results showed that in Costa Rica there is a favorable environment for the creation of a public policy in clusters development, however, before creating it, training should be promoted for the future graduates and collaborators of the companies. As for technology platforms, a greater urgemust be given to generate innovations and developments for the companies that will participate within the clusters.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresa, 2018.
Keywords: Clúster; Política; Talento humano; Tecnología; Plataformas